Effect of Dalugha (Cyrtosperma merkusii) Debris Supplementation on Hemoglobin, Cholesterol and Blood Glucose Levels in Broiler Chickens - Debby J.J. Rayer; Emma Mauren Moko; Dino Rahardiyan; Anita C.C Tengker; Christny F. Rompas; Livana Dethris Rawung (Jurnal Ilmiah Sains, 2023)
Feed is an important factor that influences the chicken's development and growth. Meanwhile, dalugha debris is a by-product of dalugha processing which is expected to be a source of feed for the growth and development of broiler chickens. The good feed can optimize metabolic processes in the animal so that it can support the process of growth and development of the animal. This study aims to determine the levels of hemoglobin, cholesterol, and blood glucose in broiler chicken that is given dalugha debris supplementation. This study used a completely randomized design (CRD), where as many as 60 docs of unsex chicken used were divided into four treatments and three replications. Each replication consisted of five chickens. The treatment given was the concentration of dalugha debris at several doses: 0%, 0.065%, 0.13%, and 0.26%. The parameters observed were hemoglobin, cholesterol, and blood glucose levels. The results showed that the provision of dalugha debris in the feed significantly (p<0.05) affected the blood glucose level, but did not affect the cholesterol and hemoglobin levels (p>0.05) of the broiler chicken. Keywords: Broiler chicken; blood biochemistry; Cyrtosperma merkusii